Opportunities of Moral Education through Lessons - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 1993)
The article proposes the importance of value education as one of the most important functions of education. To be able to get along with people, to understand each other and their behaviour, seek wise self-realization no less important than a good knowledge of mathematics or languages. On the other hand, functions of moral and general education are inseparable, because only their interface ensures successful development and its universally understandable part – knowledge. One cannot love or experience what one does not know, but knowledge gained without love and experiences will be superficial. Thus, any subject in the classroom, must not be limited to education, training. Educational opportunities lie not only in the contents, but also in the method used by the teacher, the assessment, and in particular the relationships. There are no lessons without a relationship: the teacher–students, teacher–student, student–student, student–group. All these aforementioned aspects might seem self-evident, but it should be noted that without careful planning lessons, the anticipation of objectives of not only education, but also moral education, situations to experience moral values, moral education function of a lesson can be poorly expressed.